Senecio pseudodensiserratus (Asteraceae, Senecioneae), a new species from China - Tong, Tian-Jing; Tang, Ming; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
Senecio pseudodensiserratus (Asteraceae, Senecioneae), a new species from Muli, southwestern Sichuan, China, is described and illustrated. It is closely similar to S. densiserratus, a species mainly occurring in northern Sichuan and southeastern Gansu, China, but differs by having nodding and larger capitula.